2014
DOI: 10.1089/gtmb.2013.0363
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Poly (ADP-Ribose) Polymerase-1 Genetic Variants as a Possible Risk for Allergic Rhinitis

Abstract: Recent studies point toward the involvement of poly (ADP-ribose) polymerase-1 (PARP-1) in the pathogenesis of allergic airway inflammation, such as asthma and allergic rhinitis (AR). It has been suggested that inhibition of PARP-1 provides significant protection against systemic or tissue inflammation in animal models. The objective of this study was to investigate whether single-nucleotide polymorphisms of PARP-1 gene are associated with genetic susceptibility to AR. We studied the effect of promoter variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In haplotype analysis, PARP-1 C410T, G1672A and Val762Ala polymorphisms were not associated with an increased risk for AR. These results proved that the promoter G1672A polymorphism of the PARP-1 gene may be a risk factor for AR in Turkish population [79] (Tables 1 and 2). Graves' Disease (GD) is an organ specific autoimmune thyroid disorder characterized by diffuse goiter, hyperthyroidism, dermopathy, and an ocular disorder.…”
Section: Allergic Rhinitissupporting
confidence: 60%
See 1 more Smart Citation
“…In haplotype analysis, PARP-1 C410T, G1672A and Val762Ala polymorphisms were not associated with an increased risk for AR. These results proved that the promoter G1672A polymorphism of the PARP-1 gene may be a risk factor for AR in Turkish population [79] (Tables 1 and 2). Graves' Disease (GD) is an organ specific autoimmune thyroid disorder characterized by diffuse goiter, hyperthyroidism, dermopathy, and an ocular disorder.…”
Section: Allergic Rhinitissupporting
confidence: 60%
“…The pathogenesis of AR and other allergic diseases are developed by the exposure to irritating complex substances and in response to respiratory allergens [79].…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…In sensitized mice genetic ablation of PARP-1 or its enzymatic inhibition reduces inflammation and neutrophil infiltration, ameliorating allergic airway reactions, dyspnea and asthma-associated remodeling [109,110]. In humans, a PARP-1 gene polymorphism (Val762Ala) was reported to be associated with a decreased risk of asthma [111], while PARP-1 activation is increased in PBMC and lung tissues from asthmatic patients [112].…”
Section: Pathogenic Role In Non-cancer Diseasesmentioning
confidence: 99%
“…In recent years, the association of PARP1 gene with human diseases has been investigated extensively. Epidemical studies have indicated that the variations or polymorphism of PARP1 gene can affect the risk of some human disease, such as cancers, tourette syndrome, Alzheimer's disease, asthma and allergic rhinitis [27][28][29][30][31]. However, the effect of PARP1 gene on human Values are frequency (no.…”
Section: Discussionmentioning
confidence: 99%